Intra-articular application of pulsed radiofrequency combined with viscosupplementation for improvement of knee osteoarthritis symptoms: a single centre prospective study. (17th November 2018) - Filippiadis, D.; Velonakis, G.; Mazioti, A.; Konstantos, C.; Brountzos, E.; Kelekis, N.; Kelekis, A.
Abstract: Objectives: To prospectively evaluate the effectiveness of intra-articular application of pulsed radiofrequency (PRF) combined with viscosupplementation in patients with knee osteoarthritis suffering from chronic pain refractory to conservative therapies. Methods: During a 30-month period, PRF combined with viscosupplementation was performed on 53 cases of knee osteoarthritis (45 patients, 8/45 with bilateral knee osteoarthritis). Pre-operational imaging included standard knee X-rays on anterior–posterior and lateral views used to evaluate patients according to the Kellgren–Lawrence classification. Pain, prior, one week/one, 6 and 12 months post were compared by means of a numeric visual scale (NVS) questionnaire. Results: Mean pain score prior to PRF was 8.19 ± 1.4 NVS units. This score was reduced to a mean value of 2.47 ± 2.5 NVS units at 1 week after, 2.55 ± 2.6 at 1 month, 3.1 ± 2.8 at 6 months and 5.02 ± 3.09 at 12 months of follow-up ( p < 0.01). Overall mobility improved in 47/53 (88.6%) patients. No complication was observed. Conclusions: Combining PRF with viscous supplementation is an effective and safe technique for palliative management of chronic pain in patients with knee osteoarthritis. Results seem to be reproducible and long lasting. There seems to be a need of repeating the session at 1 year.